Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.14527/pegegog.2020.007
|View full text |Cite
|
Sign up to set email alerts
|

An extensive evaluation study of the English preparatory curriculum of a foreign language school

Abstract: The study aimed to evaluate the English preparation curriculum at Aydın Adnan Menderes University School of Foreign Languages according to the Bellon and Handler model. The study was designed as a “case study”, which aimed to obtain qualitative and quantitative data from the selected case. 310 English preparation class students, 26 English lecturers, 26 lecturers of other departments and 24 students of other departments participated in the study. The data were gathered through a scale, questionnaire, interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…The final objective setting has been carried out to determine the goals that will be achieved after implementing the program, even though it is not written in an official document. Correspondingly, the lack of documents in determining the objectives is similar to the English language program, such as the AADU program, which does not have clear documents or program objectives; this has resulted in a lack of communication between stakeholders (Aktaş & Gündoğdu, 2020). The result of the research states that there is a good communication between the coordinator and program implementer about program planning, but the preparation of the documents is one of the crucial aspects in program planning, which aims to anticipate problems.…”
Section: Contextmentioning
confidence: 99%
“…The final objective setting has been carried out to determine the goals that will be achieved after implementing the program, even though it is not written in an official document. Correspondingly, the lack of documents in determining the objectives is similar to the English language program, such as the AADU program, which does not have clear documents or program objectives; this has resulted in a lack of communication between stakeholders (Aktaş & Gündoğdu, 2020). The result of the research states that there is a good communication between the coordinator and program implementer about program planning, but the preparation of the documents is one of the crucial aspects in program planning, which aims to anticipate problems.…”
Section: Contextmentioning
confidence: 99%
“…First of all, it is reported that English is not taught as a means of communication but as a discipline such as Mathematics, Social Sciences or Sciences (British Council & Turkey Economic Policies Research Foundation TEPAV, 2014). Another issue is that the teaching context is not proper for students to be motivated and not get anxious, there is no certain approach or flexibility with the curriculum (Aslan & Şahin, 2020;Demirpolat, 2015;Karcı Aktaş & Gündoğdu, 2020). There are studies on English teaching and learning during and after Covid-19, and in a hybrid context that reveal the problems.…”
Section: International Journal Of Languages' Education and Teachingmentioning
confidence: 99%